Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{3x - 2y - 4 = 0}[/tex]
[tex]\mathsf{2y = 3x - 4}[/tex]
[tex]\mathsf{y = \dfrac{3x}{2} - \dfrac{4}{2}}[/tex]
[tex]\mathsf{y = \dfrac{3x}{2} - 2}[/tex]
[tex]\mathsf{y = mx + n}[/tex]
[tex]\mathsf{m = \dfrac{3}{2} \iff n = -2}[/tex]
[tex]\mathsf{m + n = \dfrac{3}{2} + (-2)}[/tex]
[tex]\mathsf{m + n = \dfrac{3}{2} -2 }[/tex]
[tex]\mathsf{m + n = \dfrac{3 - 4}{2}}[/tex]
[tex]\boxed{\boxed{\mathsf{m + n = -\dfrac{1}{2}}}}[/tex]